Benarkah Praperadilan Menguji Aspek Formil (Analisis Hukum Penetapan Tersangka dalam Putusan Nomor: 01/Pid.Pra//2021/PN.Tob) - Ernest Sengi (Universitas Batanghari Jambi, 2022)
The determination of the suspect is the object of pretrial after the decision of the Constitutional Court Number 21/PUU-XII/2014. Pretrial only examines formal aspects; however the object of the pretrial relating to the determination of the suspect, the pretrial examination becomes a dilemma because it is always related to the examination of the fulfillment of the evidence which has actually entered the area of examination of the case material. In this paper, the legal issue being studied is the Pretrial Decision Number 01/Pid.Pra/2021/PN.Tob. who decides to reject the applicant’s pretrial application. On the other hand, the alleged criminal case can’t be tried until now because the Public Prosecutor continuously returns the file (P-19) on the grounds that there is not enough evidence. To answer these legal issues, a normative legal research method with a case approach is used. This approach is to analyze the basis of judgesconsiderations in making decisions. The results of the study show that the Pretrial Decision Number 01/Pid.Pra/2021/PN.Tob. did not consider in detail the Determination Of The Suspect. The judge does that so as not to get cought up in the examination of the case material; even though the determination of the suspect should have checked the fulfillment of the evidence in the framework of the formal aspect of the examination.